Standard versus hypofractionated intensity-modulated radiotherapy for prostate cancer: assessing the impact on dose modulation and normal tissue effects when using patient-specific cancer biology. (4th February 2021) - Her, E J; Ebert, M A; Kennedy, A; Reynolds, H M; Sun, Y; Williams, S; Haworth, A
Abstract: Hypofractionation of prostate cancer radiotherapy achieves tumour control at lower total radiation doses, however, increased rectal and bladder toxicities have been observed. To realise the radiobiological advantage of hypofractionation whilst minimising harm, the potential reduction in dose to organs at risk was investigated for biofocused radiotherapy. Patient-specific tumour location and cell density information were derived from multiparametric imaging. Uniform-dose plans and biologically-optimised plans were generated for a standard schedule (78 Gy/39 fractions) and hypofractionated schedules (60 Gy/20 fractions and 36.25 Gy/5 fractions). Results showed that biologically-optimised plans yielded statistically lower doses to the rectum and bladder compared to isoeffective uniform-dose plans for all fractionation schedules. A reduction in the number of fractions increased the target dose modulation required to achieve equal tumour control. On average, biologically-optimised, moderately-hypofractionated plans demonstrated 15.3% (p-value: <0.01) and 23.8% (p-value: 0.02) reduction in rectal and bladder dose compared with standard fractionation. The tissue-sparing effect was more pronounced in extreme hypofractionation with mean reduction in rectal and bladder dose of 43.3% (p-value: < 0.01) and 41.8% (p-value: 0.02), respectively. This study suggests that the ability to utilise patient-specific tumour biology information will provide greater incentive to employ hypofractionation in the treatment of localised prostate cancer with radiotherapy. However, to exploit the radiobiological advantages given by hypofractionation, greater attention to geometric accuracy is required due to increased sensitivity to treatment uncertainties.